2000
DOI: 10.1046/j.1439-0272.2000.00357.x
|View full text |Cite
|
Sign up to set email alerts
|

The HOS test and its relationship to fertility in the stallion

Abstract: The hypo-osmotic test has been used successfully on equine semen and was considered to be a simple and accessible method which could be a useful addition to routine equine semen analysis. It was therefore of interest to determine whether the hypo-osmotic test is significantly correlated to proposed criteria of fertility. The stallions were divided into two groups on the basis of threshold levels of fertility. A significant difference (P<0.05) was found between the two groups for the following parameters: progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 4 publications
(5 reference statements)
2
36
0
4
Order By: Relevance
“…Nevertheless, even though the potential fertility of semen is difficult to predict accurately on the basis of a single assay, we agree with the statement of Neild et al (2000) that the development of simple, inexpensive, more comprehensive assays that cover different sperm functions continues to be of interest. In this way, unlike to what is necessary to perform the evaluation with fluorescence probes, hypo-osmotic test requires fewer materials and can be quickly accomplished in field, demanding only a phase contrast microscope.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Nevertheless, even though the potential fertility of semen is difficult to predict accurately on the basis of a single assay, we agree with the statement of Neild et al (2000) that the development of simple, inexpensive, more comprehensive assays that cover different sperm functions continues to be of interest. In this way, unlike to what is necessary to perform the evaluation with fluorescence probes, hypo-osmotic test requires fewer materials and can be quickly accomplished in field, demanding only a phase contrast microscope.…”
Section: Discussionsupporting
confidence: 79%
“…As we known motility has a high correlation with fertility, which makes the execution of these two tests on the pre-freezing breeding soundness exam so important. Neild et al (2000), also evaluated if HOST in raw semen could be correlated with stallion fertility and concluded that there is a good correlation with HOST progressive motility of the raw semen (r = 0.82, P = 0.0001). Despite HOS test was not correlated with the percentage of pregnant mares (r = 0.08, P = 0.75), there was a tendency to correlate with the number of services per pregnancy (r = -0.40; P = 0.08).…”
Section: Discussionmentioning
confidence: 99%
“…Após esse período, 15 μL dessa solução foram avaliados em câma-ra úmida, sob microscopia de contraste de fase, em aumento de 400x. Foram contadas 100 células, considerando-se a presença ou ausência de cauda enrolada (Neild et al 2000). O cálculo da reação da reação hiposmótica foi realizado pela fórmula: HOST= (% de caudas enroladas após o HOST) -(% de caudas enroladas antes do HOST) conforme Melo & Henry (1999).…”
Section: Avaliação Da Motilidade Total (Mt) E Progressiva (Mp)unclassified
“…Also, the percentages of sperm motility, swollen heads, and coiled tails of BB and WNZ rabbit spermatozoa in hypo-osmotic solution at 37 o C for 20 min were significantly (P<0.01) higher in winter (14.4, 42.7, and 38.5%) than those obtained during the summer season (9.8, 33.7, and 26.6%), respectively. When understanding the changes that spermatozoa are subjected to in a hypo-osmotic environment, if we accept the suggestion that these changes indicate a functionally intact plasma membrane, and that this is necessary for normal spermatozoal function, then, within a semen sample, the more cells with swollen plasma membranes, the better the potential sperm quality (Neild et al, 2000). In addition, it was evident that the advancement of the incubation time at 37 0 C for up to 20 min decreased the grades and percentages of progressive sperm motility and increased the percentages of spermatozoa with swollen heads and coiled tails for all experimental groups with regards to main effects or interactions.…”
Section: Response Of Spermatozoa To Hostmentioning
confidence: 99%